Selective Fasciectomy in Dupuytren’s Contracture: An Experience of A Specialized Tertiary Hospital in Bangladesh - Islam, Md Ashraful; Begum, Ismat Ara; Arifeen, Khandker Md Nurul; Datta, Manoshi; Ali, Sk Mohammad; Amin, SM Yousuf; Haque Khan, Md Zahidul (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Dupuytren’s disease is a benign yet disabling, irreversible, progressive fibroproliferative condition affecting the palm and fingers, leading to flection contracture of metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints. Objective: To evaluate results of selective fasciectomy to correct the deformity of MCP and PIP joints and observe the complications. Methods: This crosssectional study was done on 30 patients of Dupuytren’s contracture treated by selective fasciectomy, between January 2015 and December 2018, in Department of Orthopaedic Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Selective fasciectomy was done under brachial plexus block, tourniquet control and loupe magnification. Brunner zigzag incision was used. Indications for surgery was MCP flection contracture more than 30⁰ and any degree of PIP flection contracture. Postoperatively hand was immobilised in extension of MCP and PIP joints for 2 weeks and then active and passive movements were encouraged and intermittent splinting for 10 weeks (only at night in last 6 weeks). Results: Among 30 patients, 24 (80%) patients were male, 6 (20%) were female; mean age was 62 years (56-74 years). 12 (40%) cases were bilateral, ring and little fingers involvement were seen in most cases (92%). Mean MCP correction was 53⁰ and mean PIP correction was 34⁰ (p<0.001). There were 3 digital nerve injuries peroperatively which were repaired/reconstructed and protective sensation regained in repaired nerve area at 1 year and 3 (10%) marginal skin loss postoperatively which healed secondarily. Superficial wound infection developed in 3 (10%) patients which healed on dressing and antibiotics. Complex regional pain syndrome developed in 2 (6.66%) patients which were mild and resolved on conservative management. 3 (10%) patients developed scar sequilae which were mild and resolved on conservative treatment. Radial digital artery injury was observed in 1 (3.33%); however, no ischaemic insult was observed postoperatively. 2 (6.66%) patients developed recurrence of the disease who were more than 70 years old; however, they declined further intervention. Conclusion: Selective fasciectomy is an easy and effective procedure with less complication to correct the deformities and improve the gripstrength significantly in Dupuytren’s contracture patients. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 41-46